Importance of extracutaneous organ involvement in determining the clinical severity and prognosis of incontinentia pigmenti caused by mutations in the IKBKG gene. Issue 5 (10th March 2021) - Kim, Hwa Young; Song, Hyun Beom; Kim, Kyu Han; Kim, Jeong Hun; Chae, Jong‐Hee; Kim, Man Jin; Seong, Moon‐Woo; Ko, Jung Min
Abstract: Incontinentia pigmenti (IP) is a rare X‐linked skin disease caused by mutations in the IKBKG gene, which is required for activation of the nuclear factor‐kappa B signalling pathway. Multiple systems can be affected with highly variable phenotypic expressivity. We aimed to clarify the clinical characteristics observed in molecularly confirmed Korean IP patients. The medical records of 25 females confirmed as IP by molecular genetic analysis were retrospectively reviewed. The phenotypic score of extracutaneous manifestations was calculated to assess the disease severity. The IKBKG gene partial deletion or intragenic mutations were investigated using long‐range PCR, multiplex ligation‐dependent probe amplification and direct sequencing methods. Among the 25 individuals, 18 (72%) were sporadic cases. All patients showed typical skin manifestations at birth or during the neonatal period. Extracutaneous findings were noted in 17 (68%) patients; ocular manifestations (28%), neurological abnormalities (28%), hair abnormalities (20%), dental anomalies (12%), nail dystrophy (8%). The common exon 4–10 IKBKG deletion was observed in 20 (80%) patients. In addition, five intragenic sequence variants were identified, including three novel variants. The phenotype scores were highly variable, ranging from abnormal skin pigmentation only to one or more extracutaneous features, although no significant difference was observed for each clinical characteristic between the group with sequence variants and that with common large deletion. Our cohort with IP showed heterogeneity of extracutaneous manifestations and high incidence of sporadic cases. Long‐term monitoring with multidisciplinary management is essential for evaluating the clinical status, providing adequate genetic counselling and understanding the genotype‐phenotype correlation in IP.